Spanish government rocked by leaked recordings scandal - Inés Fernández-Pontes (Euractiv, 2025)
Leaked recordings suggesting a smear campaign against Spain’s top anti-corruption investigators have sparked accusations of a “dirty war” by Sánchez’s government, fuelling a political crisis.